2013
DOI: 10.1061/(asce)me.1943-5479.0000163
|View full text |Cite
|
Sign up to set email alerts
|

Project Complexity Mapping in Five Dimensions for Complex Transportation Projects

Abstract: Traditional three-dimensional project management theory is based on optimizing the cost-schedule-technical dimensions. Recent studies in the United Kingdom, Canada, and Australia have shown that the current project management body of knowledge may not be adequate to address interrelated and dependent variables encountered on complex projects. This paper reports the findings of an international research team's detailed study of 18 complex projects, which confirms the findings of the previous research and propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 8 publications
1
35
0
Order By: Relevance
“…A programme of this magnitude creates a level of complexity that is difficult to evaluate using classical quantitative research methods. Thus, the study patterned itself after the methodology proposed by Gransberg, Shane, Strong, and del Puerto (2013) for complex projects. Furthermore, it is acceptable to use a single case study as a basis for scientific generalization as the purpose is to generalize the found procedures and behaviour (yin, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…A programme of this magnitude creates a level of complexity that is difficult to evaluate using classical quantitative research methods. Thus, the study patterned itself after the methodology proposed by Gransberg, Shane, Strong, and del Puerto (2013) for complex projects. Furthermore, it is acceptable to use a single case study as a basis for scientific generalization as the purpose is to generalize the found procedures and behaviour (yin, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…These complexities have led organizations to often fail to complete projects within a set time frame, approved by the budget, and in accordance with the quality required. In other words, projects in recent years have often failed or have poor performance in achieving their goals (Giezen et al, 2015;Gransberg et al, 2012;He et al, 2015). Under such circumstances, the traditional project management practices that have been used up so far are no longer able to control the emerging complexity of the projects (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we identified the storyworlds occurring in the macro environment external to the IDS projects, which included global, regional, sectoral and organizational issues. There are various approaches to defining the dimensions (Baccarini 1996;Gransberg et al 2013;Hass 2009a;Remington & Pollack 2007;Williams 2002) developed to identify the nature, or source, of the complexity (Remington et al 2009). This model assists CPMs to diagnose the complexity profile of a project, and in line with this, what level of project leadership (competencies) is needed, and therefore what problem-solving approaches are required, to manage those specific dimensions (Hass 2009a).…”
Section: Application Of the Storytelling Diamond Modelmentioning
confidence: 99%